Subsoil drainage system / Muhammad Amirul Asraf Mohd Nordin - Mohd Nordin, Muhammad Amirul Asraf (2016)
The problem according to the issue water ponding problem at SJKT Dengkil, the problem located between block c and block d. The water ponding problem must be solve for make sure not have any problem on future time. To get the building that survive in the long run, subsoil drainage installation is a good choice to choose for the water ponding problem. When the problem not be solve, it can give other problem. The example is foundation movement, crack at the wall and other thing. Foundation is a very important thing to take care. It very dangerous when have water. The problem must be solve to ensure full building functionality and safety to the occupancy of the building.